Kolaboratif PKM Internasional Mobility Consortium Pengelolaan Komunikasi Pemasaran Melalui Digitalisasi Bisnis Di Thailand - Cahyani, Nani; Puspitasari, Ratih; Hertati, Lesi; Hidayat, Janthy; Nurfaiza, Nabila (LPPM Universitas Bina Sarana Informatika, 2024)
This service activity was carried out in Thailand in the context of joint International PKM in order to realize effective marketing communications management which is the key to business success in the current digital era. Collaboration in the field of business digitalization offers great opportunities for economic growth and wider market penetration. This PKM aims to explore how collaboration in the PKM International Mobility Consortium can encourage innovation in the field of marketing communications management through business digitalization in Thailand. Through a qualitative approach with in-depth interviews and content analysis, collecting data from business stakeholders, academics and practitioners in Thailand. The pretest and posttest results show that collaboration in the International PKM consortium encourages the exchange of knowledge and resources between organizations from various countries, enriching local perspectives with a global view. Business digitalization developed through collaboration results in more adaptive and effective marketing communications strategies, enabling MSMEs in Thailand to reach a wider audience and increase competitiveness in the global market.